An overview of a biopsychosocial model of epigenetics and pain catastrophizing. Issue 3 (12th June 2019) - Brecht, Danielle M.; Gatchel, Robert J.
Abstract: In an earlier Special Issue in the Journal of Applied Biobehavioral Research (JABR), Gatchel ( Journal of Applied Biobehavioral Research, 2017, 22[1], e12088) addressed the construct of pain catastrophizing (PC). The present article is meant to extend those reviews within a biopsychosocial context, as well as update recent research on PC with a specific concentration on genetic factors. An overview of biological factors as they relate to PC and epigenetics are reviewed first (brain areas associated with pain and how they adapt neurochemically to chronic noxious stimuli, polymorphism of various genes, etc.), proceeded by the discussion of psychological (depression, anxiety, and the genomic link to neuroticism) and social influences (reason people engage in PC, age's impact on neuronal restructuring) as they corroborate the argument of PC's link to genetic factors. Finally, this article concludes by providing future directions for research concerning PC such as examining the efficacy of Pain Neurobiology Education, as well as gene therapy.